Strategi Pemasaran Klinik Utama X di Cirebon Menggunakan Pendekatan Komparatif 4P dan 4C Berbasis Matriks SWOT - Muhammad Zul Fahmi Akbar; Ela Nurlaela (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The highly competitive healthcare industry in Cirebon poses a significant challenge for Klinik Utama X, especially as a non-BPJS facility. This condition requires a paradigm shift from a provider-centric marketing mix to a patient-centric approach to retain patient loyalty. This study aims to evaluate and formulate the marketing strategy of Klinik Utama X using a comparative 4P (Product, Price, Place, Promotion) and 4C (Customer Solution, Customer Cost, Convenience, Communication) approach based on SWOT analysis. This research used a qualitative descriptive design with purposive sampling, gathering primary and secondary data through in-depth interviews, observations, and document studies. The data were systematically evaluated using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The findings reveal that the clinic is strategically positioned in Quadrant I, with an IFAS score of 2.53 and an EFAS score of 2.60, indicating strong internal capabilities to seize external opportunities. The recommended aggressive growth strategy involves integrating psychiatric and aesthetic services, penetrating the Business-to-Business (B2B) market through corporate medical check-ups, accelerating digitalization via telemedicine and online queuing, and preparing for BPJS accreditation. The managerial implications suggest that the clinic must prioritize resolving internal human resources and strengthening financial record-keeping systems before investing heavily in medical assets, while actively expanding digital convenience and corporate partnerships to secure short-term financial stability.